(untitled) (Latakia University Journal -Basic Sciences Series, 2020)
This study provides a new model for estimating the phase relations in spinel-bearing peridotite using the geothermobarometry software “Thermocalc” in the system NCFMASCr. This system is large enough to provide a simulation for phase relations in spinel-bearing peridotite and to eliminate classic spinel barometry issues. The phase relations for the spinel-peridotite xenoliths composition (from Al-Ghab depression) have been modeled by calculating the bulk-rock composition via relating mineral compositions with its modes, and then the phase diagram “P-T pseudosection” has been created. The stability field of the paragenesis: cpx + opx + ol + sp (forming the xenoliths) defined a domain of temperature ranging from 900 to 1360 ◦C and pressure ranging from 7.5 to 21 Kbar. Using the “Isomode” method, it has been concluded that mineral modes were equilibrated at a temperature of about 1130 ◦C and a pressure of about 9.5 Kbar. The estimated depth of the xenoliths origin is about 32 km corresponding to almost upper limit of the upper mantle in Al-Ghab volcanism. The results have been compared to the previous documented data calculated using classic geothermobarometry, and the differences have been interpreted as Thermocalc can show the role of pressure and temperature-sensitive elements such as Chromium and Aluminum in changing the upper limit of stability of the paragenesis cpx + opx + ol + sp only if the appropriate compositions were chosen in the dataset during calculation processes; and this, couldn’t be done using classic methods.